Marketplace Responsibility in the Sales of Super KW Bag Products Based on MUI Fatwa No. 1/5/2005 and Law No. 20 of 2016 concerning Trademarks - Aflia Ramadhani Srg; Zulkifli Nas (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The phenomenon of increasing circulation of counterfeit products such as super KW bags on marketplace platforms has caused new problems. This problem not only has an impact on the infringement of the intellectual property rights of brand owners, but also harms consumers and causes unfair business competition and even violations of religious norms. This study aims to analyze the form of marketplace responsibility in the sale of KW bag products based on legal, moral, social and religious products. This research includes doctrinal research, namely deductive normative juridical with a conceptual approach and statute approach. Primary data sources are laws and regulations related to this title, while secondary data sources are books and journals related to this research. Data is collected through document studies that include primary and secondary legal materials, then all data is analyzed qualitatively with deductive reasoning. The results of the study show that marketplaces have legal, moral, social and religious responsibilities to prevent the circulation of counterfeit goods. Marketplaces have legal, moral, social and religious responsibilities to prevent and overcome the circulation of counterfeit products such as super KW bags that are widely sold on digital platforms. Juridically, the marketplace's responsibility is not to market counterfeit products, including super KW bags. Its moral responsibilities are to maintain honesty and transparency, supervise and control sellers, provide consumer protection, educate consumers and business ethics, avoid fraudulent practices and comply with sharia principles. Its social responsibility is the verification and screening of sellers and products, providing certainty and transparency of information to consumers, providing education and prevention efforts, cooperation with authorities, brand owners, and the public. Furthermore, his religious responsibility is that he is responsible to Allah SWT for the actions of tadlis, ghasab, and gharar that he has done by repentance and not repeating the sale of KW products, including KW bag products.